“If I were the mother…”: fostering perspective taking in German teacher education - Pöhler, Maike; Briese, Fiona J.; Kinder, Annette (Frontiers in Education, 2024)
Higher perspective taking skills are associated with better social functioning and improved social relationships. Generally, teachers are willing to take the perspective of their students, but it is unclear whether the same is true for the perspective of parents. As communication and conflicts with parents are pervasive, the motivation and willingness to adopt the perspective of parents in counseling situations should be promoted during university teacher training. Therefore, we investigated the promotion of perspective taking among teachers in training and focused mainly on perspective taking towards parents. We developed a casebased learning task in which teachers in training from Freie Universität Berlin (N = 515) prepared for a fictitious upcoming consultation with a mother about her son. Because it is unclear if direct instruction for perspective taking is necessary in order to promote it, we also used indirect instruction to investigate whether preparing for the consultation under these instructions fostered the willingness to adopt the perspective of students and parents. In the direct instruction participants were directly told to take the perspective of the fictitious mother when evaluating and developing formulations for the consultation. The indirect instruction did not mention the concept of perspective taking but asked participants to focus on the comprehensibility of the formulations. We obtained three measures: the willingness to take a perspective, the attitude towards another person, and the emotional and empathic language used in written texts. With our main result we demonstrated that the willingness to adopt the perspective of both students and parents could be significantly promoted by both instructions. We further demonstrated that a higher willingness to take another's perspective is associated with a more positive attitude towards the mother, as well as increased positive emotions and empathic concern. Additionally, we replicated results of a previous study showing a generally higher willingness to take the student perspective prior to the intervention. Results are discussed regarding the benefits of promoting perspective taking, especially towards parents, in teacher education.